Awareness Development and Usage of Mobile Health Technology Among Individuals With Hypertension in a Rural Community of Bangladesh: Randomized Controlled Trial - Jahan, Yasmin; Rahman, Md Moshiur; Faruque, Abu S G; Chisti, Mohammod Jobayer; Kazawa, Kana; Matsuyama, Ryota; Moriyama, Michiko (JMIR Publications, 2020)
BackgroundHypertension (HTN) is a major modifiable risk factor and the leading cause of premature deaths globally. The lack of awareness and knowledge have been identified as risk factors in low- and middle-income countries including Bangladesh. Recently, the use of mobile phone SMS text messaging is found to have an important positive impact on HTN management. ObjectiveThe study aimed to develop awareness and knowledge in order to enhance lifestyle behavior changes among individuals with HTN in a rural community of Bangladesh by using health education and mobile health (mHealth) technology (SMS text messaging). MethodsA prospective randomized 5-month intervention, open-label (1:1), parallel-group trial was implemented among the individuals with HTN aged 35 years or older. Both men and women were included. Between August 2018 and July 2019, we enrolled 420 participants, selected from a tertiary level health facility and through door-to-door visits by community health workers. After block randomization, they were assigned to either the intervention group (received SMS text messaging and health education; n=209) or the control group (received only health education; n=211). The primary outcome was the evaluation of self-reported behavior changes (salt intake, fruits and vegetables intake, physical activity, and blood pressure [BP], and body weight monitoring behaviors). The secondary outcomes were measurements of actual salt intake and dietary salt excretion, blood glucose level, BP values, and quality of life (QOL). ResultsDuring the study period, a total of 8 participants were dropped, and the completion rate was 98.0% (412/420). The adherence rates were significantly higher (9%) among the control group regarding salt intake (P=.04) and physical activity behaviors (P<.03), and little differences were observed in other behaviors. In primary outcome, the focused behavior, salt intake less than 6 g/day, showed significant chronological improvement in both groups (P<.001). The fruits intake behavior steadily improved in both groups (P<.001). Participants in both groups had a custom of vegetables intake everyday/week. Physical activity suddenly increased and continued until the study end (P<.001 in both groups). Both BP and body weight monitoring status increased from baseline to 1 month but decreased afterward (P<.001). In case of secondary outcomes, significant chronological changes were observed in food salt concentration and urinary salinity between the groups (P=.01). The mean systolic BP and diastolic BP significantly chronologically decreased in both groups (systolic BP, P=.04; diastolic BP, P=.02.P<.05). All of these supported self-reported behavior changes. For the QOL, both groups showed significant improvement over the study periods (P<.001). ConclusionsBased on these results, we suggest that face-to-face health education requires integration of home health care provision and more relevant and timely interactive SMS text messages to increase the effectiveness of the intervention. Besides, community awareness can be created to encourage "low-salt culture" and educate family members. Trial RegistrationBangladesh Medical Research Council (BMRC) 06025072017; ClinicalTrials.gov NCT03614104; https://clinicaltrials.gov/ct2/show/NCT03614104 and UMIN-CTR R000033736; https://tinyurl.com/y48yfcoo International Registered Report Identifier (IRRID)RR2-10.2196/15523